Musical feedback system Jymmin® leads to enhanced physical endurance in the elderly—A feasibility study - Rehfeld, Kathrin; Fritz, Thomas Hans; Prinz, Alexander; Schneider, Lydia; Villringer, Arno; Witte, Kerstin (Frontiers in Sports and Active Living, 2022)
Background and objectives Active music-making in combination with physical exercise has evoked several positive effects in users of different age groups. These include enhanced mood, muscular effectivity, pain threshold, and decreased perceived exertion. The present study tested the applicability of this musical feedback system, called Jymmin®, in combination with strength-endurance exercises in a population of healthy older adults. Research design and methods Sixteen healthy, physically inactive older adults (5 males, 11 females) at the mean age of 70 years performed physical exercise in two conditions: A conventional work-out while listening passively music and a Jymmin® work-out, where musical sounds were created with one's work-out movements. According to the hypothesis that strength-endurance is increased during musical feedback exercise, parameters relating to strength-endurance were assessed, including exercise duration, number of repetitions, perceived exertion (RPE), and participants' mental state (Multidimensional Mood State Questionnaire; MDMQ). Results Results show that participants exercised significantly longer while doing Jymmin® (Mdn = 248.75 s) as compared to the conventional work-out (Mdn = 182.73 s), (Z = 3.408, p = 0.001). The RPE did not differ between conventional work-out and the Jymmin® condition, even though participants worked out significantly longer during the Jymmin® condition (Mdn = 14.50; Z = −0.905; p = 0.366). The results of the MDMQ showed no significant differences between both conditions (Z = −1.037; p = 0.300). Discussion and implications Results show that participants could work out longer while showing the same perceived exertion, relating to increased physical endurance. Music feedback work-out encouraged a greater degree of isometric contractions (muscle actively held at fixed length) and, therefore, less repetitions in this condition. In addition to the previously described effect on muscle effectivity, this non-stereotypic contraction pattern during music feedback training may have enhanced endurance in participants supporting them to better proportion energetic reserves during training (pacing). Clinical trial registration Identifier: DRKS00023645.